Virgilian underworlds in A. S. Byatt's The Children's Book. (6th April 2016) - Stevens, Benjamin Eldon
Abstract : A. S. Byatt's The Children's Book envisions life as a kind of afterlife, living death, or living burial in part by developing images of the journey into the underworld, katabasis, as depicted in Virgil's Aeneid. Although Virgil is not Byatt's only source, she has found in him not only compelling particular images (including the Sibyl's possession by Apollo, the elm hung with false dreams, Tartarus, and the gates of ivory and horn) but also a more generally meaningful metaphysics of confinement and inescapability. In the master metaphor, the underworld is both literal and figurative, with what lies below the earth illuminating what lies beneath a person's surface. By exploring this aspect of Byatt's novel, we stand to learn more about her Virgilianism (as examined by scholars including Cox, Slater, and others) and, so, about Virgilian receptions in contemporary fiction .